GLOBAL TABLOID culture and technology. - Conboy, Martin; Eldridge, Scott A., II ([S.l.] : ROUTLEDGE, 2021)
This edited collection brings together a range of contemporary expertise to discuss the development and impact of tabloid news around the world. In thirteen chapters, Global Tabloid covers tabloid developments in Asia, Africa, the Americas, Australia, and both Eastern and Western Europe. It presents innovative research fromeighteen expert contributors and editors who explore tabloidization as a phenomenon, and tabloids as a news form. With an awareness of historical dynamics where tabloids played a role in national news media systems, it brings the debates around tabloids as a cultural force up to date. The book addresses important questions about the contemporary nature of popular culture, the challenges it faces in the digital era, and its impact on a political world dominated by tabloid values. Going beyond national borders to consider global developments, the editors and contributors explore how the tabloids have permeated media culture more generally and how they are adapting to an increasingly digitalized media sphere. This internationally focused critical study is a valuable resource for students and researchers in journalism, media, and cultural studies.
OCLC-licensed vendor bibliographic record.
Keywords: Tabloid newspapers -- Social aspects; Sensationalism in journalism; Social media; SOCIAL SCIENCE / Media Studies